Walt Whitman's Western Jaunt - Eitner, Walter H. (University Press of Kansas, 1981)
In 1879, when Walt Whitman was sixty, he made a trip to the West-first to Kansas to attend the quartercentennial celebration of Kansas settlement, then on to Denver and the Rockies. Biographers have only briefly reported this trip, if they have dealt with it at all; here for the first time is a thorough reconstruction of Whitman's western experience. From his own extensive research in newspapers of the period, as well as from Whitman's published daybooks and notebooks and his collected correspondence. Walter H. Eitner is able to piece together a well detailed itinerary, and to compare the record of the actual journey with Whitman's imaginative account in Specimen Days.This study in part constitutes a criticism of the sections of Specimen Days dealing with the West by examining the ways in which Whitman reordered his experiences to have them support a bardic pose he wished to maintain. For the first time Whitman's three journalist traveling companions-whom Whitman did not even mention in Specimen Days-are fully on record. This account also shows Whitman very much his own press agent, engaging in a wide range of selfpromoting activities such as writing his own interviews and sending back to the press in the East accounts of his whereabouts, his health, and his plans.